2013
DOI: 10.1111/anec.12101
|View full text |Cite
|
Sign up to set email alerts
|

Brugada Phenocopy Clinical Reproducibility Demonstrated by Recurrent Hypokalemia

Abstract: Brugada phenocopies (BrP) are clinical entities that are etiologically distinct from true congenital Brugada syndrome (BrS). BrP are characterized by type 1 or type 2 Brugada electrocardiogram (ECG) patterns in precordial leads V1 -V3 ; however, BrP are elicited by various underlying clinical conditions such as electrolyte disturbances, myocardial ischemia, or poor ECG filters. In this report, we describe the first case of clinically reproducible BrP which is important to the conceptual evolution of BrP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
(36 reference statements)
0
10
0
1
Order By: Relevance
“…A negative result of provocative testing with sodium channel blockers (e.g., flecainide, procainamide, or ajmaline) is another criterion in the updated definition of Brugada phenocopy. 3,4 Moreover, the concomitant overdose of heroin and alcohol makes it difficult to ascertain that the Brugada phenocopy is solely due to heroin overdose.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A negative result of provocative testing with sodium channel blockers (e.g., flecainide, procainamide, or ajmaline) is another criterion in the updated definition of Brugada phenocopy. 3,4 Moreover, the concomitant overdose of heroin and alcohol makes it difficult to ascertain that the Brugada phenocopy is solely due to heroin overdose.…”
Section: Discussionmentioning
confidence: 99%
“…The role of Brugada phenocopy in heroin overdose and its association with clinical outcomes, such as sudden cardiac death, is unclear; however, physicians, especially in emergency department, should be particularly vigilant about such ECG changes, and to report any suspicious case of ECG changes to evaluate "clinical reproducibility" of our observation. 4 This should be regarded in milieu of steadily increasing prevalence of heroin abuse that has risen from 373,000 in 2007 to 669,000 in 2012. 13 The White House Office of National Drug Control Policy recently reported that the number of overdose deaths involving heroin increased by 45% between 2006 and 2010.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the type‐1 Brugada ECG pattern is diagnostic for BrS, the type‐2 Brugada ECG pattern requires differential diagnosis from conditions that produce a similar morphology . These include normal variant because of inadvertent placement of leads in the second and third intercostal space, incomplete right bundle branch block (IRBBB), healthy athletes, pectus excavatum, arrhythmogenic right ventricular dysplasia (ARVD), electrolyte abnormalities, and early repolarization . The ECG is an important tool in the evaluation of cardiac disease and although it appears to be relatively archaic, it continues to prove itself as a valuable instrument in the diagnosis of complex arrhythmic disease.…”
mentioning
confidence: 99%
“…We have published extensively on the subject of BrP and have established the international etiological categories and diagnostic criteria for BrP. The etiological categories are: (i) metabolic conditions, (ii) mechanical compression, (iii) ischemia and pulmonary embolism, (iv) myocardial and pericardial disease, (v) ECG modulation, and (vi) miscellaneous.…”
mentioning
confidence: 99%